Maximizing Paper Fibre Recovery Using Property Cascade Analysis Technique - Muhamad Moza, Muhamad Mohtar (2012)
Paper can be broadly classified into two types which high fibre paper and low fibre paper. In paper manufacturing, every stage of the paper production and consumption cycle is associated with a range of potential environmental problems. In addition, trees’ harvesting to produce the paper contribute to global warming. Therefore, one of possible ways to solve this problem is by recycling the papers. In fact, paper fibre recovery options can give great impact in reducing climate change, greenhouse gases, forest preservation, water and air pollution, waste management and energy problems. Hence, this research is to establish the minimum paper fibre targets using property cascade analysis (PCA) for a paper making process after looking at the possibility of using the available fibre sources within the process to meet its fibre demands. In order to find the maximum paper recovery, constructing the property cascade table from the limiting paper fibre data is needed. The property cascade analysis eliminates any tedious steps of graphical technique and quickly yield the exact utility targets and the pinch location in order to achieve the minimum fibre targets during network design. The fresh fibre target was estimated at 1464.27 tons per year which having a reduction of 43.68% of fresh fibre.